Rising Medical Liability Cost and Patient Access to Care in Puerto Rico: Public Survey - Cruz, Norma I.; Korchin, Leo; Castro, Gilberto (Puerto Rico Health Sciences Journal, 2011)
Objective: The high cost of medical liability increases healthcare expenditure and decreases healthcare services. To understand the public perception of medical liability issues in Puerto Rico, a survey was made with the assistance of Gaither International. Methods: Five hundred interviews were made in a representative sample of all six US Census demographic regions in Puerto Rico. Respondents were selected randomly by age, gender, socioeconomic level and region of residence. All had visited an Emergency Room in the past two years, either for their medical needs or those of a family member. This study requested information on general demographics, use of emergency medical services, insurance coverage, access to medical care, and perception of the medical liability issues. All results had a margin of error of ±4.4 with a 95% confidence level. Results: When rating areas of concern in healthcare, “cost of health insurance and services” was greatest, followed by “difficulty finding a specialist”. One-third of respondents experienced difficulty or failed to obtain a specialist, orthopedic surgeons topping the list. When asked who benefits most from lawsuits, 63% of the public believed that lawyers benefit most, while only 33% believed that the patient (plaintiff) benefits most. In the interviews, 84% of respondents supported establishing government limits on professional liability awards as part of the effort to reduce healthcare cost. Conclusion: The public appears to be aware of how medical liability raises the cost and limits access to healthcare.